The Anti-proliferation Effect of an Isolated Butanol Fraction of Tampa Badak (Voacanga foetida (Bl.) K. Schum) Leaves on Leukemia, Lung, and Cervical Cancer - Susanty, Adriani; Dachriyanus, Dachriyanus; Yanwirasti, Yanwirasti; Sri Wahyuni, Fatma; Sekar, Andisyah Putri; Alimin, Nur; Magdazaleni, Magdazaleni; Sofia, Sri Esky; Dewi, Citra Kartika (Pharmaceutical Sciences and Research, 2020)
Voacanga foetida (Bl.) K.Schum leaves are known to have cytotoxic activity against blood cancer cells. This study was aimed to determine the potential of an isolated butanol fraction of Voacanga foetida (Bl.) K.Schum leaves (Tb3 compound) in inhibiting the proliferation of several cancer cells, including leukemia (K562), lung cancer (A549), and cervical cancer (He-La) using the dye exclusion method. We found that the percentage of anti-proliferation of the Tb3 compound was increased in a dose-dependent manner, where it showed 83% (K562), 72.3% (He-La), and 70.7% (A549) inhibition at higher concentration. These values were relatively higher compared to doxorubicin as a positive control, 77.1%, 63.8%, and 62.7%, respectively. Moreover, the IC50 values of the Tb3 compound were still in the range of active cytotoxic compounds based on NCI classification, which is less than 4 µg/mL; 0.5 μg/mL, 2.4 μg/mL, and 3.6 μg/mL for K562, A549, and He-La, respectively. Therefore, this study indicated the potential anticancer effect of an isolated butanol fraction of the Tb3 compound to inhibit cancer cell proliferation, which provides an alternative for cancer therapy.